A functional bread designed with rye flour and stevia sweetener: A sensory and microbiological annalysis (2018)
Rye flour bread is a relatively new development. This product is a functional food rich in flavonoids, mucilage, pentosans, vitamins and minerals. Additionally, rye-based products have previously shown to improve acute postprandial appetite ratings, appear to lower glucose and insulin response and decrease voluntary food intake at a subsequent meal. Compared to whole white bread, it prevents inflammation of both, gastrointestinal and respiratory mucosa, being an excellent nutritional option feasible to be included in our daily diet. The aim of this research was to develop a functional bread from rye flour and stevia with three formulations: 50, 60 and 80% of rye flour. The microbiological, physicochemical and sensory assessments were made, evidencing that 50/50 formula was the best accepted by the evaluators. According to NTC 1363 norm the product was classified as a soft bread with fiber, since fiber was (35.8%) and the moisture obtained was (35.65%). In microbiological analysis, the results showed that it is a suitable product for human consumption and taste, texture and presentation analysis, this product was well-rated by the consumers, concluding that, is suitable to be merchandise as an alternative to wheat bread in daily human standard meals.